Relationship between psychological empowerment, physical activity enjoyment, and response to a HIIT Program in physically inactive young women: a prospective multicentre study - Irene Ferrando-Terradez; Rodrigo Núñez-Cortés; Laura López-Bueno; Enrique Alcántara; Joaquín Calatayud; José Casaña; Ivana Parčina; Lirios Dueñas (BMC Women's Health)
Abstract Background This study aimed to investigate the relationship of psychological empowerment and enjoyment of physical activity with changes in physical activity levels, sleep quality, and muscular endurance following a high-intensity interval training (HIIT) program in physically inactive young women. Methods A total of 61 physically inactive young women (age: 20.1 ± 2.7 y) were recruited to participate in a six-month HIIT intervention delivered via a smartphone app. Outcome measures included physical activity levels (MET-min/week), muscular endurance (plank test), and sleep quality through the Pittsburgh Sleep Quality Index (PSQI). The Healthy Lifestyle and Personal Control Questionnaire (HLPCQ) and the Physical Activity Enjoyment Scale (PACES) were used to assess psychological empowerment and enjoyment, respectively. Repeated measures ANOVA and covariate analyses were performed to evaluate the impact of the intervention and the role of psychological empowerment and enjoyment. Results At 6 months, significant improvements in physical activity (p < 0.001; ηp²=0.336) and muscular endurance (p = 0.005; ηp²=0.085) were observed, with large and moderate effect sizes, respectively. The PACES showed a significant interaction with time for MET-min/week (F = 11.67, p = 0.001, ηp²=0.129), suggesting that enjoyment influenced the increase in physical activity. No significant differences in sleep quality were observed (p > 0.05). Conclusion Enjoyment plays a crucial role in the response to HIIT programs among physically inactive young women, particularly in improving weekly physical activity levels. Psychological training showed no significant relationship with the outcomes studied.